PDFGuardian: An innovative approach to interpretable PDF malware detection using XAI with SHAP framework - Rahman, Tahsinur; Ahmed, Nusaiba; Monjur, Shama; Haque, Fasbeer Mohammad; Kabir, Naweed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.